[Acknowledgement of success of actions that led to the discovery and liquidation of a wide-ranging enemy network.] (1943)
This memo outlines the results of an operation to disrupt and arrest Russian and Norwegian operatives in the Kirkenes area. Taken from microfilm Records of the German Field Command, Armies, National Archives Series T-315, Reel 1621m Annex 1b, KTB No. 3, 210 Infantry Division, folder 45787/2, first frame 000165. Translated by Major James F. Gebhardt, USA (retired)